Evaluation of P5RA Independent Curriculum on the Character of Santriwati MA As'adiyah Putri Sengkang - Kartini Kartini; Misykat Malik Ibrahim; Muhammad Nur Akbar Rasyid (Prodi PAI STIT Sunan Giri Bima, 2025)
This study aims to evaluate the implementation of Merdeka Curriculum in the P5RA program and its effect on the development of santriwati's state and religious characters at Madrasah Aliyah As'adiyah Putri Sengkang. this study was conducted using the Countenance Stake evaluation model. Using a qualitative approach, data were collected through observation, in-depth interviews, and documentation. Research participants included the head of madrasah, teachers, and santriwati. Data analysis followed the Countenance Stake model, which consists of three stages: antecedent (input), transaction (process), and outcome (result). The findings show that: (1) In the antecedent phase, madrasah shows adequate readiness to implement the P5RA program under the Merdeka Curriculum, supported by careful preparation and planning; (2) In the transaction phase, the P5RA learning process is effectively implemented through various project-based activities that integrate Pancasila and Islamic values; and (3) In the outcome phase, the results obtained are in accordance with the expected goals. Nevertheless, improvements are needed in strengthening documentation, enhancing teacher training, enriching learning projects, optimizing the use of technology, developing evaluation instruments, and strengthening collaboration networks to ensure the long-term sustainability and effectiveness of the P5RA program at Madrasah Aliyah As'adiyah Putri Sengkang.